It’s too quick to blame myself—the effects of fast and slow rates of change on credit assignment during object lifting - Fercho, Kelene; Baugh, Lee A. (Frontiers in Human Neuroscience, 2014)
Although there have been substantial research efforts examining the effect of various rates of change in reaching movements, there has been little to no research devoted to this issue during object manipulation tasks. In force-field and visuomotor adaptation studies, two parallel processes have been identified: First, a fast process that adapts and de-adapts quickly is thought to enable the actor to deal with potentially transient perturbations. Second, a slower, but longer lasting process adapts if these initial perturbations persist over time. In a largely separate body of research, the role of credit assignment has been examined in terms of allotting the cause of errors to changes in the body vs. changes in the outside world. Of course, these two processes are usually linked within the real world, with short lasting perturbations most often being linked to external causes and longer lasting perturbations being linked to internal causes. Here, we demonstrate that the increases in load forces associated with a gradual increase in object weight during a natural object lifting task are transferred when lifting a novel object, whereas a sudden increase in object weight is not. We speculate that gradual rates of change in the weight of the object being lifted are attributed to the self, whereas fast rates of change are more likely to be attributed to the external environment. This study extends our knowledge of the multiple timescales involved in motor learning to a more natural object manipulation scenario, while concurrently providing support for the hypothesis that the multiple time scales involved in motor learning are tuned for different learning contexts.